The Effect Of The Learning-By-Doing Strategy On Acquiring And Retaining Geographical Concepts Among Third-Grade Middle School Female Students In Social Studies (Journal of the College of Basic Education, 2026)
The research aims to demonstrate the impact of the learning-by-doing strategy on acquiring and retaining geographical concepts among third-grade middle school female students in social studies. The experimental method was employed, and a sample of 60 students was selected, divided into two groups: the first group, consisting of 30 students, was taught using the work-based learning strategy, while the second control group, also consisting of 30 students, was taught using the conventional method.A research tool was developed, comprising a concept acquisition test consisting of 30 multiple-choice items. After the test and the experiment were completed, appropriate statistical methods were used, revealing a statistically significant difference at the 0.05 significance level between the average scores of the students in the experimental group studying geography according to the (L.B.D) strategy and the average scores of the third-year intermediate female students studying the same subject according to the traditional method.Several conclusions were reached, the most significant being that the use of the work-based learning strategy has an effect on enhancing the level of acquisition of geographical concepts. Furthermore, several recommendations were made, the most important being the generalisation of the work-based learning strategy to other educational stages and subjects, in addition to expanding research and studies on the work-based learning strategy.